Hydrogen-induced cracking and corrosion behavior of friction stir welded plates of API 5L X70 pipeline steel - Giarola, J. M.; Calderón-Hernández, J. W.; Quispe-Avilés, J. M.; Avila, J. A. [UNESP]; Bose Filho, W. W. (Elsevier, 2021)
The use of friction stir welding (FSW) has proven to be an excellent alternative to join engineering components. Although FSW has had a significant development in recent years, challenges for new applications have been raised, such as offshore steel parts suffering hydrogen embrittlement in the gas and oil industry. Therefore, in this work, the microstructure, corrosion, and hydrogen-induced cracking were investigated in a two-pass FSW welded joint of API 5L X70 pipeline steel. The electrochemical results indicate an inhibitory effect on corrosion reaction because of a carbonate product generation in the steel surface. The polygonal ferritic and degenerated pearlite bands microstructure in the base metal fixed carbonate deposits in the steel surface. In the welded regions, the bainitic microstructure and the carbide particle distribution are less efficient in setting the weld surface carbonate deposit. HIC tests showed cracks initiation and propagation to be more prone in hard phases.
Keywords: API 5L X70; Corrosion resistance; Friction stir welding; HIC; LEIS; Potentiodynamic polarization tests